Hodnocení obsahu pesticidů v zemědělských půdách Jihomoravského kraje - Mádrová, Anna (Vysoké učení technické v Brně. Fakulta chemická, 2023)
Tato bakalářská práce se zabývá problematikou pesticidů v půdě. Hodnotí obsah reziduí pesticidů v zemědělských půdách Jihomoravského kraje za období 2015-2021. Rezidua pesticidů byla sledována v rámci Bazálního monitoringu zemědělských půd, analýza probíhala metodou kapalinové chromatografie shmotnostní detekcí. Monitoring provádí Ústřední kontrolní a zkušební ústav zemědělský, který také poskytl veškerá data pro tuto práci. Pro hodnocení byly vybrány nejčastěji nalezené látky – 2-hydroxyatrazin, boskalid, diflufenikan, dimoxystrobin, epoxykonazol, prochloraz, tebukonazol a 2-hydroxytebuthylazin. Nejvyšší koncentrace byla naměřena u boskalidu. Nejčastěji byl detekován epoxykonazol. Nalezené koncentrace pesticidů v Jihomoravském kraji jsou ve srovnání se Zlínským krajem a krajem Vysočina i několikanásobně nižší.

This bachelor's thesis deals with the issue of pesticides in soil. It evaluates the concentration levels of pesticide residues in agricultural soils in the South Moravian Region in 2015-2021. Pesticide residues were monitored as a part of the Basal Soil Monitoring System, the concentrations were determined by liquid chromatography–mass spectrometry. The monitoring is performed by the Central Institute for Supervising and Testing in Agriculture (ÚKZÚZ), which also provided all the data for this work. The most frequently detected substances were selected for evaluation – 2-hydroxyatrazine, boscalid, diflufenican, dimoxystrobin, epoxiconazole, prochloraz, tebuconazole and terbutylazine-2-hydroxy. The highest concentration was measured for boscalid. Epoxyconazole was the most frequently detected substance. The concentrations of pesticide residues found in soils of the South Moravian Region are several times lower compared to the Zlín Region and the Vysočina Region.
Assessment of pesticide content in agricultural soils of the South Moravian Region
Keywords: pesticidy; přípravky na ochranu rostlin; zemědělské půdy; Bazální monitoring zemědělských půd; Jihomoravský kraj; pesticides; plant protection products; agricultural soils; Basal Soil Monitoring System; South Moravian Region